Review of community-based interventions for people with serious mental illness, focusing on learning instrumental activities of daily living and enhancing wellbeing - Emi Patmisari; Yunong Huang; Carla McLaren; Pankhuri Bhatia; Mark Orr; Sumathi Govindasamy; Emily Hielscher; Helen McLaren (Scandinavian Journal of Occupational Therapy)
This review synthesises evidence on community-based interventions designed to support individuals with serious mental illness (SMI) in learning instrumental activities of daily living (IADLs). Given the increasing prevalence of SMI affecting over 500 million people worldwide, and associated functional impairments, effective interventions are critically needed. This review of thirty studies represented a range of global contexts and intervention types, which were categorised into simple IADLs (e.g. household chores), complex IADLs (e.g. financial management), and recreational IADLs (e.g. leisure activities). Findings demonstrated that community-based interventions significantly improved IADLs, promoting functional independence and overall well-being. Thematic analysis identified five key mechanisms for success: individualised goal-setting, structured programs with practical learning, engagement of support systems, integration into daily life, and use of innovative technologies. The review highlighted that personalised and practical IADL interventions, supported by robust community and technological resources, were most effective. When effective, interventions enhance practical skills of individuals while also contributing to emotional well-being, social connections, and personal fulfilment. Despite promising results, the review notes variability in study designs and outcomes, suggesting a need for consistent and long-term evaluations. Nonetheless, review insights offer valuable guidance for designing future interventions to better support autonomy and community integration of individuals with SMI.